A Case Study to Dissect Immunity to SARS-CoV-2 in a Neonate Nonhuman Primate Model - Fovet, Claire-Maëlle; Pimienta, Camille; Galhaut, Mathilde; Relouzat, Francis; Nunez, Natalia; Cavarelli, Mariangela; Sconosciuti, Quentin; Dhooge, Nina; Marzinotto, Ilaria; Lampasona, Vito; Tolazzi, Monica; Scarlatti, Gabriella; et al. (Frontiers in Immunology, 2022)
Most children are less severely affected by Coronavirus-induced disease 2019 (COVID-19) than adults, and thus more difficult to study progressively. Here, we provide in a neonatal non-human primate (NHP) a deep analysis of early immune responses to SARS-CoV-2 infection in blood and mucosal tissues. In addition, we provide a comparison with SARS-CoV-2 infected adult NHP. Infection of the neonate resulted in a mild disease compared to adult NHPs that develop, in most cases moderate lung lesions. In concomitance with the viral RNA load increase, we observed the development of an early innate response in the blood, as demonstrated by RNA-sequencing, flow cytometry and cytokine longitudinal data-analyses. This response included the presence of an antiviral type-I IFN genes-signature, a persistent and lasting NKT cell population, a balanced peripheral and mucosal IFN-/IL-10 cytokine-response and an increase in B cells that was accompanied with anti-SARS-CoV-2 antibody response. Viral kinetics and immune responses coincided with changes in the microbiota profile-composition in the pharyngeal and rectal mucosae. In the mother, viral RNA loads were close to quantification limit, despite the very close contact with SARS-CoV-2-exposed neonate. This pilot study demonstrates that neonatal NHPs are a relevant model for pediatric SARS-CoV-2 infection permitting insights into early steps of anti-SARS-CoV-2 immune responses in infants.